Representações sociais de usuários sobre o Programa Saúde da Família - Ana Paula Azevedo Hemmi (2008)
This is a qualitative study case based on the Theory of Social Representations and the aim is to grasp the social representations of the users about the Family Health Program. Seven users were interviewed, two men and five women, all around the age of 70. All of them havebeen living in the area around the Basic Health Units of Belo Horizonte, in the northeast of the city, for about ten years. The main question of the interview was "What do you understand about the Family Health Program". The interview finished with the data saturation. Discourse Analysis was used to interpret the data, the interviews weresystematically read until the definition of the corpus and the representations of the users were organized in two categories: 1- when the access to health programs took a long time and the services were bad; 2- new ways to do and represent health services. The firstcategory is related to the period before the implementation of the program in Belo Horizonte and the second is related to what happened after this implementation. Through these two categories we can see that there were changes that can be noticed through the users discourse and these changes favor the services in the Basic Health Units. The representations of the users about the Family Health Program are not defined by therecognition of names or symbols created by health professionals but they are defined by the notion acquired by the users when they look for the services. The users are able to see the transformation through which the services are passing, what reflects upon the new forms of representation of the program besides the memory of the times before the programimplementation. The end of the long lines and the links between the users and the health professionals made the Basic Health Units a social space for activities. The research can be useful to make the health professionals reflect about the importance of knowing the valuesand beliefs of the users and about their involvement in the programs for its success.